N-Acetyltransferase 2 status and gastric cancer risk: a preliminary meta-analysis (Italian Journal of Public Health, 2005)
In recent studies N- Acetyltransferase 2 (NAT2) genotype has been considered as a risk factor for developinggastric cancer, however with conflicting results among Asian and Caucasian populations. In order to clarifythe influence of NAT2 slow acetylation status on gastric cancer risk, a preliminary meta-analysis of publishedcase-control studies was undertaken. The primary outcome measure was the odds ratio (OR) for the risk ofgastric cancer associated with the NAT2 slow genotype using a random effects model. Pooling the resultsfrom the 5 studies identified (771 cases, 1083 controls), an overall OR for gastric cancer risk associated withthe NAT2 slow genotype of 0.91 emerged (95% CI: 0.54-1.55). The result suggests that the NAT2 slowgenotype has probably no effect on the risk of gastric cancer. Additional epidemiological studies, based onsample sizes that are commensurate with the detection of small genotypic risks, are required to confirmthese findings. Future studies may also help to clarify whether geographic differences exist.
Keywords: gastric cancer; genetic epidemiology; N- Acetyltransferase 2; meta-analysis